The effect of beta-oxidation or TCA cycle inhibition on mitochondrial function and the sensitivity of high resolution respiratory detection - Osiki, Prisca Ofure (Department of Human Biology, 2020)
INTRODUCTION: A dysfunction in fatty acid beta-oxidation (β-oxidation), particularly medium chain acyl-CoA dehydrogenase (MCAD) dysfunction is a major cause of mortality and its diagnosis is usually achieved by measuring specific protein activities or metabolites in blood and/or urine samples. However, these methods do not account for secondary defects that accompany primary deficiency; such as where measures of disruption in fatty acid metabolism do not account for defects in the TCA cycle and oxidative phosphorylation. These metabolic pathways are connected and dysfunction in one pathway (primary) could lead to dysfunction in the other (secondary). We propose the use of methods that combines all aspects of the bioenergetics module (enzyme activity in substrate oxidation within each individual pathway, transfer of electrons through the electron transport system (ETS) and oxidative phosphorylation for ATP generation) may be a more effective assessment technique. High resolution respirometry (HRR) is a recently developed technique that accounts for substrate oxidation, electron transfer via the ETS and oxidative phosphorylation. It measures the rate of oxygen consumption or flux at different respiratory states when appropriate substrates, uncouplers and inhibitors (SUIT protocols) are used. With this method, two substrate combinations are commonly used to assess medium-chain fatty acid β-oxidation; a) Octanoylcarnitine and carnitine, which is partial to the β-oxidation cycle alone, and b) Octanoylcarnitine and malate, which assesses the influence of the TCA cycle. Additionally, a combination of pyruvate, glutamate and malate is used to assess oxidation within the TCA cycle. We investigated the sensitivity of commonly used substrate combinations in HRR assessment to detect changes in mitochondrial respiration and dysfunction induced by the inhibition of either β-oxidation or the TCA cycle in C2C12 myotubes. Furthermore, we assessed MCAD, citrate synthase and aconitase enzyme activities when β-oxidation or TCA cycle was inhibited in C2C12 myotubes. METHODS: C2C12 myotubes were differentiated for 6 days and treated for 12 hours with a high or a low concentration of one of two inhibitors as follows; a) 2 mM or 8 mM 2-mercaptoacetate to inhibit medium chain acyl-CoA dehydrogenase (MCAD); b) 6 mM or 9 mM fluorocitrate to inhibit aconitase. Each treatment was compared to control myotubes grown for the same length of time without the addition of inhibitors. The activities of MCAD, aconitase and citrate synthase were determined. In addition, mitochondrial respiration measured as O2 flux at Routine, Leak, OXPHOS and ETS respiratory states were assessed in an Oxygraph-2K after inhibition or in control treatments using; i) Octanoylcarnitine and carnitine ii) Octanoylcarnitine and malate iii) pyruvate, malate and glutamate substrate combinations. For each assessment we corrected O2 flux recorded at each state to; a) approximate number of cells (pmol O2/s/million cells) b) protein concentration (pmol O2/s/mg protein) c) Flux control ratio (FCR) of each state to the maximum ETS capacity; ETSFAO+CI+CII (convergent electron flow from Fatty acid oxidation (FAO), Complex I (CI) and CII) d) FCR to either FAO-linked ETS capacity; (ETSFAO) or CI-linked ETS capacity (ETSCI). RESULTS: Treatment of cells with either a low or high concentration of 2-mercaptoacetate to inhibit MCAD resulted in no significant difference in MCAD activity. Fluorocitrate treatment decreased aconitase activity with low treatment (p = 0.011) compared to control, and conversely it increased MCAD activity in high treatment compared to control (p = 0.024). Both 2-mercaptoacetate (p = 0.03) and fluorocitrate (p < 0.01) treatment at high concentrations resulted in increased citrate synthase activity, compared to low concentration and control. Mitochondrial respiration with octanoylcarnitine and carnitine substrate combination was not altered with MCAD or aconitase inhibition. Octanoylcarnitine and malate substrate combination showed a decrease in mitochondrial respiration at the following respiratory states with both MCAD and aconitase inhibition; Routine (p = 0.01), LeakFAO (p = 0.029), OXPHOSFAO (p = 0.006), ETSFAO (p = 0.008), ETSFAO+CI (p = 0.017). FCR of each state to the maximum capacity (ETSFAO+CI+CII) revealed a decrease with both MCAD and aconitase inhibition at the following states; routine (p = 0.001), OXPHOSFAO (p = 0.003), ETSFAO (p = 0.018), ETSFAO+CAR (p = 0.008) and ETSFAO+CI (p = 0.027). Pyruvate, malate and glutamate substrate combination showed decreased mitochondrial respiration with MCAD inhibition at the following respiratory states; Routine (p = 0.004), LeakCI (p = 0.007), OXPHOSCI (p = 0.003), ETSCI (p = 0.003), ETSCI+FAO (p = 0.01) and ETSCI+FAO+CII (p = 0.003). FCR of each state to the maximum capacity (ETSCI+FAO+CII) decreased with both MCAD and aconitase inhibition at Routine (p = 0.024), OXPHOSCI (p = 0.024) and ETSCI (p = 0.035) states. DISCUSSION: The main finding of this study was related to two of the SUIT protocols 1) octanoylcarnitine and malate, and 2) pyruvate, malate and glutamate. These protocols were sensitive in showing decreased respiratory capacity and coupling control ratios and may be appropriate for assessing changes in oxidative metabolism when there is a defect in β-oxidation and/ or the TCA cycle. On the other hand, octanoylcarnitine and carnitine substrate combination is not sensitive to detect dysfunction induced by inhibition of either β-oxidation or TCA cycle. Irrespective of the enzyme inhibited, HRR detected dysfunction in complex I (CI), although, when aconitase was inhibited, reduced CI-linked respiration was more pronounced compared to MCAD inhibition. Furthermore, primary inhibition of MCAD to inhibit β-oxidation may have caused secondary inhibition of TCA cycle via aconitase, shown in decreased TCA cycle CI-linked respiration where MCAD was inhibited. In contrast, primary inhibition of aconitase seemed to be compensated for by increased MCAD activity and mitochondrial respiration related to β-oxidation. Lastly, enzyme assaysshould not be used as standalone techniques for assessing metabolic dysfunction at the level of TCA, β-oxidation and the mitochondria since they are not sensitive to low level defects, nor do they account for secondary interactions that influence either TCA or betaoxidation. HRR is useful to assess mitochondrial respiration and dysfunction, when using an appropriate substrate combination and should be used in combination with the more traditional enzyme activity assays.